2022
DOI: 10.1039/d1cp04286f
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structure and curious motions in 1,1-difluorosilacyclopent-3-ene and silacyclopent-3-ene as determined by microwave spectroscopy and quantum chemical calculations

Abstract: The molecules 1,1-difluorosilacyclopent-3-ene (3SiCPF2) and silacyclopent-3-ene (3SiCP) have been synthesized and studied using chirped pulse, Fourier transform microwave (CP-FTMW) spectroscopy. For 3SiCP this is the first ever microwave study of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is confirmed from the experimental structure with the exception that some atoms, particularly the silicon, are very near the b and c axis, both complicating the accuracy of the Kraitchman coordinate position and giving larger errors in those coordinates. This proximity and large uncertainty in the dihedral angle is very similar to that observed in 1,1-difluorosilacyclopent-3-ene, which had doubling in some transitions possibly due to an unidentified motion. No such doubling was observed in these spectra, however, which led the authors to conclude that the large uncertainty in any dihedral angle is just due to the uncertainty in the coordinate positions as the determined values, ignoring the errors, are very close to the theoretical structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is confirmed from the experimental structure with the exception that some atoms, particularly the silicon, are very near the b and c axis, both complicating the accuracy of the Kraitchman coordinate position and giving larger errors in those coordinates. This proximity and large uncertainty in the dihedral angle is very similar to that observed in 1,1-difluorosilacyclopent-3-ene, which had doubling in some transitions possibly due to an unidentified motion. No such doubling was observed in these spectra, however, which led the authors to conclude that the large uncertainty in any dihedral angle is just due to the uncertainty in the coordinate positions as the determined values, ignoring the errors, are very close to the theoretical structures.…”
Section: Resultsmentioning
confidence: 99%
“…For this, the authors are not entirely sure because there was no additional splitting observed in either spectrum to provide a case for some form of large amplitude motion. It has been observed by the authors previously in similar systems that curious motions can exist in these silicon ring molecules, but there was no direct evidence here. This could be due to the frequency range of the experiment and warrants further study, but it was outside the capabilities available to the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation